Epithelioid glioblastoma exhibits a heterogeneous molecular feature: A targeted next-generation sequencing study - Pan, Rui; Wang, Xiaotong; Fang, Ru; Xia, Qiuyuan; Wu, Nan; Rao, Qiu (Frontiers in Oncology, 2022)
Epithelioid glioblastoma (eGBM) is one of the rare glioblastoma (GBM) variants in the current World Health Organization (WHO) classification of central nervous system (CNS) tumours. However, the diagnostic basis and molecular features of eGBM have not been clearly defined to date. In this study, we aimed to molecularly characterize these tumours. The clinical and radiological data of 12 cases of eGBM were collected, and their pathological, immunohistochemical and molecular features were examined. Headache was the main symptom. Microscopy revealed that the tumours were composed of epithelioid cells and rhabdoid cells. Six cases (50%) harboured the BRAF V600E mutation, and NF1 mutation was detected in 2 eGBM cases (16.7%). CDKN2A/B homozygous deletion was seen in 5 cases (41.7%). TP53 mutation was detected in 2 cases (16.7%), and TERT promoter mutation was detected in 5 cases (41.7%). eGBM is characterized by high molecular heterogeneity and has molecular overlaps between low-grade gliomas. Moreover, the biological significance of “epithelioid” appearance may be reduced to a simple morphological pattern rather than a variant or entity. Therefore, molecular stratification through genome-wide molecular profiling will be essential in the future for determining clinical trials of patients.